Tambores Maranhenses: do corpo africano à(há) produção de sentido da posição/condição mulher - Pacheco, Conceição de Maria dos Santos (2017)
The act of reading by the Speech Analysis theory presents the study of the African-maranhense culture expression known as Drum of Creole of Maranhão which is constituted, historical and discursively, from the drum of the slave quarters as a prayer to St. Benedict. It was observed that, throughout the research, new outspreads of the Drum of Creole of Maranhão, in genres, that happened as long as determinations, from the discourse which represents the European settler, limited these expressions which resulted in reentries under the shape of resistence, in a process of different negotiations: the fellowship, the Cultural Heritage, and the End street. The general goal was comprehend the possibilities of inscription of the position sujeito brincante coreira on the game of End Street, through the relations between memory and culture. As specific goals: interpreting the senses production process of the position sujeito coreira on the habit of dressing up and being dressed up by chita skirt; point out the slidings of the significant materialities and the effects of produced/read/interpreted/signified on the end street game. Were used in this analysis exercise the founder concepts of the Speech Analysis (PÊCHEUX, 2010), (ORLANDI, 2002) and (HENRY, 2010) with the formulations about non-identification (INDURSKY, 2007), file, rupture (ZOPPI-FONTANA, 2002), textualizing (GALLO, 2008), imbrication, significant materialities (LAGAZZI, 2009), discursive body (LEANDRO FERREIRA, 2013), artistic discourse, tecedura, tessitura, sensible projections (NECKEL, 2004 e 2010). As, the hybridism conception (HALL, 2003), miscegenation (CANCLINI, 2003), (DARCY RIBEIRO, 1995), (CATTANI, 2007) and (MUNANGA, 1999) and syncretism (FERRETI, 2013) and to welcome the brazilian africanity, was researched the Epistemology of Ancestry (OLIVEIRA, 2002) in a perspective to comprehend the discursive political movements that look back to the power fights versus resistence observed on the drums.